Information modeling and relational databases - Halpin, T. A. (Elsevier/Morgan Kaufman Publishers, 2008)
Information Modeling and Relational Databases, second edition, provides an introduction to ORM (Object-Role Modeling)and much more. In fact, it is the only book to go beyond introductory coverage and provide all of the in-depth instruction you need to transform knowledge from domain experts into a sound database design. This book is intended for anyone with a stake in the accuracy and efficacy of databases: systems analysts, information modelers, database designers and administrators, and programmers.